Orang Baduy di Banten Selatan: Manusia Air Pemelihara Sungai - Kusnaka Adimihardja (Antropologi Indonesia, 2000)
The presence of the Baduy people in Mount Kendeng in southern Banten was, in keeping with the order of Pajajaran Kingdom, to manage the continuity of the flow of the river from the upper course to the lower. At that time, the river-stream played an important role in agriculture, besides being a means of trading and transportation at the lower-course region of Banten. The Baduy had the role of guarding the equilibrium at the upper course region, and maintain the economic development of the Pajajaran Kingdom. The Baduy who live around the upper course of the river are not allowed, traditionally, 'teu wasa', to disturb the ecosystem, such as to exploit the rice fields or to dig the soil for agricultural activities. They use the expression:...gunung teu meunang dilebur, lebak teu meunang diruksak, mountains are not to be destroyed, valleys are not to be destructed, if it is disobeyed there will be great disaster upon human life. In carrying out the kingdom's orders, they are supported by a certain hierarchic and complex political system, even though they are egalitarian and keep a firm social solidarity. The stratified system of defense was bound by the tangtu tilu 'the three core of leadership'. It is also called ka-puun-an ideology systems which are located at three villages: Cikeusik, Cibeo, and Cikertawana under the guidance of moral, ethics, and rules which are stated in the values of Sunda Wiwitan religion.